A manual of the law of real property - Megarry, Robert; Oakley, A. J. (London : Sweet & Maxwell, 2002)
A textbook on the law of real property. This edition emphasizes the importance of registered land and considers the likely impact of the Land Registration Bill 2000 and the Human Rights Act 1998, as well as updating all chapters in the light of the legislation passed as well as the case law
Includes bibliographical references and index.
Keywords: Real property -- England; Real rights